IMMUNOPATHOLOGICAL EFFECT OF SENSITIZED TRANSFER FACTOR ON THE ORGANS OF WHITE MICE AGAINST SALMONELLA TYPHI CHALLENGE INFECTION. - AL-Joboury, Khalil H. (The Iraqi Journal of Veterinary Medicine, 2021)
In an experimental study to evaluate the immunopathological effect of transfer factor on the reticuloendothelial organs of white mice and their protection against their challenge infection with Salmonella typhi. The results of this study were showed the followings: 1. Transfer factor recipient group: it was showed an early granulomatous lesions in the liver. Reactive hyperplasia in the T cell regions of the spleen and mediastinal lymph node. The early granulomas were persisted during 7th day and slightly regressed on 14th day postinoculation. 2. Infected group with S. typhi: It was showed a multifocal microabscesses consisted of aggregates of neutrophils in the focal area of necrosis, which was evident during 7th day and gradually transform into granulomas on 14th day postinoculation. 3. Transfer factor recipient and challenge infection group: It was showed well developed granulomatous reactions, which indicate an emergence of cellular immunity (delayed type hypersensitivity reaction). These granulomas were more evident on 7th day and slightly regressed on 14th day postinoculation; providing a transfer factor role in tissue reaction and termination of infection.